Study on the Main Components Interaction from Flos Lonicerae and Fructus Forsythiae and Their Dissolution In Vitro and Intestinal Absorption in Rats - Zhou, Wei (Public Library of Science, 2014)
The Flos Lonicerae-Fructus Forsythiae herb couple is the basic components of Chinese herbal preparations (Shuang-Huang-Lian tablet, Yin-Qiao-Jie-Du tablet and Fufang Qin-Lan oral liquid), and its pharmacological effects were significantly higher than that in Flos Lonicerae or Fructus Forsythiae, but the reasons remained unknown. In the present study, pattern recognition analysis (hierarchical cluster analysis (HCA) and principal component analysis (PCA)) combined with UHPLC-ESI/LTQ-Orbitrap MS system were performed to study the chemical constitution difference between co-decoction and mixed decoction in the term of chemistry. Besides, the pharmacokinetics in vivo and intestinal absorption in vitro combined with pattern recognition analysis were used to reveal the discrepancy between herb couple and single herbs in the view of biology. The observation from the chemical view in vitro showed that there was significant difference in quantity between co-decoction and mixed decoction by HCA, and the exposure level of isoforsythoside and 3, 5-dicaffeoylquinic acid in co-decoction, higher than that in mixed decoction, directly resulted in the discrepancy between co-decoction and mixed decoction using both PCA and HCA. The observation from the pharmacokinetics displayed that the exposure level in vivo of neochlorogenic acid, 3, 4-dicaffeoylquinic acid, isoforsythoside and forsythoside A, higher than that in single herbs, was the main factor contributing to the difference by both PCA and HCA, interestingly consistent with the results obtained from Caco-2 cells in vitro, which indicated that it was because of intestinal absorption improvement of neochlorogenic acid, 3, 4-dicaffeoylquinic acid, isoforsythoside and forsythoside A that resulted in a better efficacy of herb couple than that of single herbs from the perspective of biology. The results above illustrated that caffeic acid derivatives in Flos Lonicerae-Fructus Forsythiae herb couple could be considered as chemical markers for quality control of its preparations.